Output-error state-space identification of vibrating structures using evolution strategies: A benchmark study - Dertimanis, Vasilis (My University, 2014)
In this study, four widely accepted and used variants of Evolution Strategies (ES) are adapted and applied to the output-error state- spaceidentification problem. The selection of ES is justified by prior strong indication of superior performance to similar problems, over alternatives like Genetic Algorithms (GA) or Evolutionary Programming (EP). The ES variants that are being tested are (i) the (1+1)-ES, (ii) the (μ/δ+λ;)-SA-ES, (iii) the (μδ,λ)-SA-ES, and (iv) the (μw,λ)-CMA-ES. The study is based on asix-degree-of-freedom (DOF) structural model of a shear building that is characterized by light damping (up to 5%). The envisaged analysis is taking place through Monte Carlo experiments under two different excitation types (stationary / non-stationary) and the applied ES are assessed in terms of (i) accurate modal parameters extraction, (ii) statistical consistency, (iii) performance under noise-corrupted data, and (iv) performance under non-stationary data. The results of this suggest that ES are indeed competitive alternatives in the non-linear state-spaceestimation problem and deserve further attention.
Keywords: Evolution strategy; Optimization; State-space; Structural identification